EVALUASI DAN PENILAIAN KINERJA PENYELENGGARAAN OTONOMI DAERAH DI WILAYAH KALIMANTAN - Said Fadhil, Baban Sobandi dan (Pusjar SKPP Lembaga Administrasi Negara, 2006)
The autocratic regime under Suharto administration (1966-1998) is widelybelieved to be the main source of regional disparity incidence. In line with the blowing of “wind of change” i.e. total reform, decentralization framework is becoming very well-liked option in promoting democracy as well as empowering local government. Nevertheless, decentralization is not cure for all illnesses. Many experts warn that only when carefully planned, effectively implemented, and appropriately managed, can decentralization lead to significant improvement in the welfare of people at the local level. On the contrary, badly planned decentralization can worsen regional inequalities. Based on such consideration, this paper supports the idea of regular evaluation on the implementation of regional autonomy policy. Strategic sectors of development are being examined in this paper, showing the real performance level of local authorities in executing autonomous tasks and power. There are two LGU’s (local government unit) to be assessed in this paper, i.e. Kota Baru District in South Kalimantan and Penajam Paser Utara District in East Kalimantan. This paper proposes to apply similar evaluationfor all district/city government in Indonesia.Keywords: evaluasi kinerja, otonomi daerah, Kota Baru, Penajam Paser Utara.